2015
DOI: 10.1167/iovs.14-14649
|View full text |Cite
|
Sign up to set email alerts
|

Near Heterophoria in Early Childhood

Abstract: Despite developmental maturation of interpupillary distance, refractive error, and AC/A, in a typical sample of young children the predominant dissociated position is one of exophoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 59 publications
5
38
0
1
Order By: Relevance
“…On average, there was less than 1 pd difference in the phoria magnitude between the alternating and the unilateral short cover protocol, while the unilateral long cover revealed larger phorias especially at the closest viewing distance in both adults and young children. These results agree with previous studies showing larger phorias after prolonged dissociation . This change in heterophoria with duration has been attributed to the decay of slow fusional vergence and so these results suggest that young children are capable of undergoing adaptation, supporting the results of other recent studies …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On average, there was less than 1 pd difference in the phoria magnitude between the alternating and the unilateral short cover protocol, while the unilateral long cover revealed larger phorias especially at the closest viewing distance in both adults and young children. These results agree with previous studies showing larger phorias after prolonged dissociation . This change in heterophoria with duration has been attributed to the decay of slow fusional vergence and so these results suggest that young children are capable of undergoing adaptation, supporting the results of other recent studies …”
Section: Discussionsupporting
confidence: 93%
“…The instrument uses default average calibration functions based on data collected from adults, but these calibration factors have been found to be variable across subjects . For this reason, individual calibrations of refractive state (lens calibration) and gaze (prism calibration) were performed for all subjects using a technique described elsewhere . The mean relative calibration slopes were similar for adults and children ( Prism calibration : Adults: −0.80 ± 0.20; Children: −0.92 ± 0.28; Lens calibration : Adults: 1.11 ± 0.22; Children: 1.04 ± 0.24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we excluded the results of the under‐10‐years age group due to the possibility of data inaccuracy, so that prevalence estimates would be as close to true values as possible. Another explanation for the higher prevalence of convergence insufficiency in children is that children may have lower accommodative convergence/accommodation (AC/A) ratios compared to adults and this may result in under‐convergence (exophoria), even in the presence of accurate accommodation at near . Furthermore, higher demand for near work (due to school work and home work) can also explain the higher prevalence of convergence insufficiency in children.…”
Section: Discussionmentioning
confidence: 99%
“…and its examination,both diatance and near, is essential to diagnose binocular disorders [1]. In 2015, Babinsky et al [2] conducted heterophroia exams on 50 children (refractive diopter: -1.25D to +3.75D) and 12 orthophoria adults, their results showed that 78% children and 69% adults manifested exophoria defined by over two prism degree, and only 20% children and 23% adults had orthophoria(the degree of deviation was within two prism degree, including each two-prism-degree exophoria and esophoria), and only one kid and one adult had esphoria over two prism degrees.…”
Section: Introductionmentioning
confidence: 99%